2017
DOI: 10.18632/oncotarget.20709
|View full text |Cite
|
Sign up to set email alerts
|

A tRNA fragment, tRF5-Glu, regulates BCAR3 expression and proliferation in ovarian cancer cells

Abstract: Ovarian cancer is a complex disease marked by tumor heterogeneity, which contributes to difficulties in diagnosis and treatment. New molecular targets and better molecular profiles defining subsets of patients are needed. tRNA fragments (tRFs) offer a recently identified group of noncoding RNAs that are often as abundant as microRNAs in cancer cells. Initially their presence in deep sequencing data sets was attributed to the breakdown of mature tRNAs, however, it is now clear that they are actively generated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 64 publications
(79 reference statements)
0
62
0
Order By: Relevance
“…Generally, there are two types of tsRNAs based on the length and cleavage sites of the tRNAs: tRNA-derived fragments (tRFs) and tRNA-derived stress-induced RNAs (tiRNAs). Interestingly, mounting evidence has shown that they are not merely byproducts of a random tRNA cleavage, but rather have critical functional roles as regulatory factors in the pathophysiologic processes of various diseases, such as tumor proliferation in ovarian cancer cells (Zhou et al, 2017) and cell cycle regulation in non-small cell lung cancer (Shao et al, 2017), and are potential biomarkers in prostate cancer (Olvedy et al, 2016). Nevertheless, to date, there are no studies focusing on the relationship between tsRNAs and traumatic SCI, and their molecular and intermolecular interactions and key signaling pathways remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are two types of tsRNAs based on the length and cleavage sites of the tRNAs: tRNA-derived fragments (tRFs) and tRNA-derived stress-induced RNAs (tiRNAs). Interestingly, mounting evidence has shown that they are not merely byproducts of a random tRNA cleavage, but rather have critical functional roles as regulatory factors in the pathophysiologic processes of various diseases, such as tumor proliferation in ovarian cancer cells (Zhou et al, 2017) and cell cycle regulation in non-small cell lung cancer (Shao et al, 2017), and are potential biomarkers in prostate cancer (Olvedy et al, 2016). Nevertheless, to date, there are no studies focusing on the relationship between tsRNAs and traumatic SCI, and their molecular and intermolecular interactions and key signaling pathways remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…tsRNAs were veri ed to be associated with numerous diseases, such as metabolic disorder, pathological stress injuries, neurodegenerative diseases, virus infection as well as cancer (9). In elds related to cancer research, expression pro le and biological function of tsRNAs were reported in chronic lymphocytic leukemia (CLL) (10,11), lung cancer (5,10,12), colorectal cancer (5, 13), breast cancer (5, 14-17), ovarian cancer (5,18,19) and prostate cancer (20,21). However, tsRNAs have not been elucidated in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…In year 2009, Cole et al first identified tRFs from cultured HeLa cells (Cole et al 2009). Then, tRFs were detected in other kinds of human cells or tissues (Zhou et al 2017;Yeung et al 2009;Wang et al 2013). tRFs were also evaluated in plants or other animals, such as barley (Hackenberg et al 2013) and cattle (Casas et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They can be classified into tRF-5, tRF-3, tRF-1, i-tRF, and tiRNA (tiRNA-3 and tiRNA-5) (Lee et al 2009;Pliatsika et al 2017). Many studies have shown that tRFs have specific biological roles and are implicated in mediating complex pathological processes of diverse illnesses, such as cancer and viral infectious disease (Zhou et al 2017;Yeung et al 2009;Guzman et al 2015). A well-studied research revealed that tRFs are associated with mammalian brain aging (Karaiskos and Grigoriev 2016).…”
Section: Introductionmentioning
confidence: 99%